Investigation of global developmental delay. Issue 8 (21st July 2006) - McDonald, L; Rennie, A; Tolmie, J; Galloway, P; McWilliam, R
Abstract : The investigation of global developmental delay in preschool children varies between centres and between paediatricians. 1 Following a literature search and review of the evidence base, guidelines were developed to assist in the assessment and management of such children presenting to secondary level services. Evidence supporting the use of genetic and biochemical investigations on a screening basis was found, but there was no evidence to support the use of metabolic investigations or neuroimaging in the absence of other positive findings on history or examination. Detailed history and examination are paramount in the assessment of children with global developmental delay. Investigations can be a useful adjunct in determining aetiology. Evidence based guidelines have been developed to assist doctors in the selection of appropriate investigations for this group of children.